2021
DOI: 10.3389/fimmu.2021.789740
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Promotes Instability of Regulatory T Cells in Antineutrophil Cytoplasmic Antibody-Associated Vasculitis

Abstract: We investigated the characteristics of regulatory T cells (Tregs), focusing on the relationship between their stability and reactive oxygen species (ROS), in antineutrophil cytoplasmic antibody-associated vasculitis (AAV). Intracellular expressions of effector cytokines, forkhead box protein 3 (FoxP3), ROS, phosphorylated mammalian target of rapamycin (mTOR), and sirtuin 1 (SIRT1) in Tregs from peripheral blood mononuclear cells (PBMCs) of patients with AAV and healthy controls (HC) were analyzed. The alterati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Studies have shown that SOD can not only remove free radicals but also regulate immune cell function, inhibit in ammatory mediators, and regulate cell signaling [10,30]. A signi cant decrease in SOD level indicates a serious oxidative stress imbalance within the body.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that SOD can not only remove free radicals but also regulate immune cell function, inhibit in ammatory mediators, and regulate cell signaling [10,30]. A signi cant decrease in SOD level indicates a serious oxidative stress imbalance within the body.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol plays a role in reducing H 2 O 2 production [ 69 ]. In people with obesity, decreasing the level of regulatory T cells caused by consuming high-fat foods can lead to an increase in the level of oxidative stress [ 70 ]. Resveratrol has been shown to play an important role in improving T-Regs function and preventing suppression of T-Regs production [ 71 ].…”
Section: Antioxidant Therapymentioning
confidence: 99%
“…Anti-neutrophil cytoplasmic antibody-associated vasculitis (AAV) is a systemic autoimmune disease involving hyperactivated neutrophils, inflammatory factors, and ROS. Shimojima et al investigated the role of Tregs in AAV and showed that SIRT1 levels, to some extent, negatively regulated the AMPK pathway through the mTOR, maintaining the stability of Tregs in AAV (144). Additionally, oxidative stress had been observed to be involved in giant cell arteritis, which was mainly maintained by the enhanced ROS production by immature neutrophils.…”
Section: Vasculitis and Giant Cell Arteritismentioning
confidence: 99%